AP-1 transcription factors mediate BDNF-positive feedback loop in cortical neurons - Tuvikene, Jürgen; Pruunsild, Priit; Orav, Ester; Esvald, Eli-Eelika; Timmusk, Tõnis (The journal of neuroscience, 2016)
Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, regulates both survival and differentiation of several neuronal populations in the nervous system during development, as well as synaptic plasticity in the adult brain. BDNF exerts its biological functions through its receptor TrkB. Although the regulation of BDNF transcription by neuronal activity has been widely studied, little is known about TrkB signaling-dependent expression of BDNF. Using rat primary cortical neuron cultures, we show that the BDNF gene is a subject to an extensive autoregulatory loop, where TrkB signaling upregulates the expression of all major BDNF transcripts, mainly through activating MAPK pathways. Investigating the mechanisms behind this autoregulation, we found that AP-1 transcription factors, comprising Jun and Fos family members, participate in the induction of BDNF exon I, III, and VI transcripts. AP-1 transcription factors directly upregulate the expression of exon I transcripts by binding two novel AP-1 cis-elements in promoter I. Moreover, our results show that the effect of AP-1 proteins on the activity of rat BDNF promoters III and VI is indirect, because AP-1 proteins were not detected to bind the respective promoter regions by chromatin immunoprecipitation (ChIP). Collectively, we describe an extensive positive feedback system in BDNF regulation, adding a new layer to the elaborate control of BDNF gene expression. - SIGNIFICANCE STATEMENT Here, we show for the first time that in rat primary cortical neurons the expression of all major BDNF transcripts (exon I, II, III, IV, VI, and IXa transcripts) is upregulated in response to TrkB signaling, and that AP-1 transcription factors participate in the induction of exon I, III, and VI transcripts. Moreover, we have described two novel functional AP-1 cis-elements in BDNF promoter I, responsible for the activation of the promoter in response to TrkB signaling. Our results indicate the existence of a positive feedback loop for obtaining sufficient BDNF levels necessary for various TrkB signaling-dependent physiological outcomes in neurons.
Gesehen am 29.05.2020